The Analysis of Stunting Risks in Pregnant Women in Maluku - Sopacua, Dian; Leutualy, Vanny; Madiuw, Devita (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2026)
Background : Stunting is still a global and Indonesian problem. Although it has decreased yearly, it is still far from the 2024 National Medium-Term Development Plan (RPJMN), which is 14%. The government has carried out various interventions, but they have not been able to reduce the incidence of stunting. Innovation is needed in handling stunting to detect the risk of stunting early in life before toddlers, namely since pregnancy. Methods : The purpose of this study is to analyze the risk factors for stunting since pregnancy. This quantitative study used a cross-sectional approach. The research sample was 100 women of childbearing age in Ambon City, and purposive sampling was used as the sampling technique. A valid and reliable instrument assessed the risk of stunting since pregnancy. This study used a chi-square test to analyze pregnant women's risk factors for stunting. Results: The results showed that 65 (65%) respondents had a moderate to high risk of stunting. Conclusions: There is a relationship between upper arm circumference, hyperemesis gravidarum, height, weight gain during pregnancy, smoking habits during pregnancy, family income, age at risk, history of exposure to cigarette smoke, and pregnancy spacing have a significant relationship with the risk of stunting since pregnancy. Health workers and cadres should be able to detect stunting risk since pregnancy using the SIDIK SIAMA instrument to prevent stunting.